Genetic regulation of recurrent spontaneous abortion in humans - Vaiman, Daniel (Biomedical Journal, 2015)
Recurrent pregnancy loss, defined as a pregnancy failure occurring before 24 weeks of gestation more than two or three times according to most definitions, is a fertility defect encountered in 1-5% of the patients. This defect is of course of multifactorial origin. Among the possible origins of recurrent pregnancy loss are uterine structural defaults, defective ploidy control of the embryo, defective immunological dialog between the embryo (or the fetus) and the uterus sometimes in relation with immunological disorders (such as autoimmune diseases), thrombophilia, and free radical metabolism imbalance. Numerous studies attempted to correlate variants of genes supposed to be intervening in the different facets of the early maternal-fetal or maternal-embryonic dialog, and eventually modify the outcome of fertilization, leading to success or failure of post-implantation development. The objective of the present review is to portray the major genes and gene polymorphisms studied for their putative association with recurrent pregnancy loss. Most of these genes have been studied as candidate genes for which strong biological arguments were put forward as to their putative involvement in recurrent pregnancy loss. They were mostly studied by genetic analysis, often in various populations of different ethnic origins, throughout the world. Some of these studies were available only in English as abstracts and were nevertheless used if the information was given with enough detail. With the space being too short to depict all the available literature, different major pathways relevant to the scientific question are presented without any attempt to hide the fact that discordant views often aroused for a given gene.